2006
DOI: 10.1194/jlr.m600127-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

ABCA7 expression is regulated by cellular cholesterol through the SREBP2 pathway and associated with phagocytosis

Abstract: ABCA7 is highly homologous to ABCA1 and mediates cellular cholesterol and phospholipid release by apolipoproteins when transfected in vitro. However, expression of ABCA7 was downregulated by increased cellular cholesterol while ABCA1 was upregulated, and the results were consistent by forced expression or downregulation of sterol-responsive/ regulatory element (SRE) binding proteins (SREBPs). We analyzed the promoter of the ABCA7 gene and identified the new exon encoding 96 bp (mouse) and 95 bp (human) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 44 publications
9
113
1
2
Order By: Relevance
“…and overexpressed (13). However, endogenously expressed ABCA7 is not expressed on the cell surface and may not be involved in HDL biogenesis (20,26). This view supports the finding that SAA does not produce HDL with the cells of ABCA1-KO mice, in which ABCA7 expression is increased (20).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…and overexpressed (13). However, endogenously expressed ABCA7 is not expressed on the cell surface and may not be involved in HDL biogenesis (20,26). This view supports the finding that SAA does not produce HDL with the cells of ABCA1-KO mice, in which ABCA7 expression is increased (20).…”
Section: Discussionsupporting
confidence: 77%
“…However, endogenously expressed ABCA7 is not expressed on the cell surface and may not be involved in HDL biogenesis (20,26). This view supports the finding that SAA does not produce HDL with the cells of ABCA1-KO mice, in which ABCA7 expression is increased (20). Therefore, there is unlikely to be an alternative pathway(s) for SAA-HDL production to the ABCA1-dependent mechanism, at least in vivo.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…To obtain a reporter construct with mutation of apoE DR4 element (DR4mu), site-directed mutagenesis was performed to introduce the DR4 at 2448 to 2433 bp of the 2690 to 19 reporter gene using a Quick Change II Site-Directed Mutagenesis Kit (Stratagene, La Jolla, CA) and the respective primers, DR4 of forward: 5′-CCGGGGATGGGGAGttaaCACCGTGGCAGAGGAATCACTA-3′, reverse: 5′-TAGTGATTCCTCTGCCACGGTGttaaCTCCC-CATCCCCGG-3′ (lowercase letters indicate mutated nucleotides). The plasmid for expression of LXRa and the reporter plasmid containing four tandem repeats of LXREs upstream of the thymidine kinase (TK) promoter and its mutant, LXRE-TK and LXREmut-TK, the promoter plasmid containing sterol regulatory element (SRE), were prepared as previously described (19,20). 3T3 cells were grown to 60-70% confluence in 24-well plates, transfected with 1 mg of plasmid DNA including 0.2 mg LXRa expression vector, 0.77 mg reporter gene construct, and 30 ng hRluc-TK (Promega; for normalization) using Lipofectamine 2000 (Invitrogen).…”
Section: Construction Of Luciferase Reporter Genes and Luciferaase Assaymentioning
confidence: 99%
“…Recent demographic studies have shown a decrease in incidences in developed countries most likely due to improved treatment and prevention of vascular risk factors 2, 3, 4. Genome‐wide association studies (GWAS) have revealed novel molecular pathways, among these the ATP‐binding‐cassette transporter A7 ( ABCA7 ),5, 6 which may be involved in both transmembrane lipid transport and phagocytosis of amyloid‐ β in the brain 7, 8, 9, 10, 11, 12, 13, 14. Following these GWAS findings, rare loss‐of‐function variants in ABCA7 were reported to confer risk of Alzheimer's disease in case–control studies in Icelandic and Belgian populations 15, 16.…”
Section: Introductionmentioning
confidence: 99%